Working with young peer researchers in sexuality studies: benefits, challenges and lessons learnt - Anna Page; Marianne Cense; Miranda van Reeuwijk (Sexual and Reproductive Health Matters)
Involvement as peer researchers provides young people with an opportunity to exercise their right to participation and can facilitate unique insights into young people’s lives, social contexts, choices and negotiations. However, evidence on the approach has to date included little in-depth discussion on the complexities presented by sexuality research. Here, engaging young people as researchers is influenced by intersecting cultural discourses, particularly regarding youth agency and sexual freedom. This article provides practice-based insights from involving young people as peer researchers within two rights-based sexuality-focused research projects in Indonesia and the Netherlands. Drawing on two contrasting cultural contexts, it explores benefits and challenges regarding youth-adult power dynamics, the taboo nature of sexuality, research quality and dissemination. Recommendations for future studies include ongoing training and capacity strengthening for peer researchers which recognise cultural and educational backgrounds, strong youth-adult partnerships creating an enabling environment for the engagement of peer researchers, careful consideration of how young people are involved and critical reflection on adult-centric views of what constitutes “academic” research.